A Case Study of Student Hooligan Behaviour during Protest Action at the University of KwaZulu-Natal (Journal of Student Affairs in Africa, 2022)
This article focuses on the behaviour of students during protest action at the University of KwaZuluNatal (UKZN). The objectives of the study on which the article is based were to assess factors that contribute to student hooliganism and to evaluate the effects of violent student protests on the university community. The data were collected using interviews with 25 purposefully sampled participants including 20 students and five risk management personnel. The data were analysed using descriptive writing and identifying actively generated themes from the participants’ responses. The study found that a private security service and the South African police service actively instigated violence on campus as a means to disperse the crowd, and that the crowd retaliated with violence. It was also found that the university management’s ignorance of students’ grievances caused students to be violent and exhibit hooligan behaviour to attract management’s attention. Victims of violence experienced physical injury and destruction of their property, which inevitably affected them psychologically, academically and behaviourally. It is recommended that security personnel are trained to control crowds without using violence, and that university management resolve student grievances promptly before they lead to violent protesting.
Keywords: Crowd control; hooliganism; protest; security services; student activism; students; university leadership; university management; violence; riot policing